2014
DOI: 10.5603/ait.2014.0003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical experience with the C-Mac videolaryngoscope in morbidly obese patients

Abstract: Background: The use of videolaryngoscopes is recommended as a part of routine practice in anaesthesia for morbidly obese patients. The aim of this study was to evaluate C-Mac in a group of morbidly obese patients to see if it improves intubation conditions. Methods: 86 morbidly obese (BMI > 40 kg m -2 ) patients scheduled for bariatric surgery were included in the study. In every studied case, C-Mac was used with a Mackintosh shaped blade. For the first attempt, the anaesthetists performing the intubation were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 9 publications
0
22
0
1
Order By: Relevance
“…After this initial laryngoscopy, the trachea was intubated with either the C-MAC or the GlideScope and the modified C-L grading was documented. The C-MAC was used as indirect laryngoscope throughout the protocol (as opposed to a direct laryngoscope [14]). When the GlideScope was used, a rigid stylet was inserted in the tracheal tube.…”
Section: Methodsmentioning
confidence: 99%
“…After this initial laryngoscopy, the trachea was intubated with either the C-MAC or the GlideScope and the modified C-L grading was documented. The C-MAC was used as indirect laryngoscope throughout the protocol (as opposed to a direct laryngoscope [14]). When the GlideScope was used, a rigid stylet was inserted in the tracheal tube.…”
Section: Methodsmentioning
confidence: 99%
“…In modern anesthesiology, the main cause of serious complications, including hypoxic brain injury is connected to difficulties with airway management and oxygenation [19]. Especially in selected groups of patients like morbidly obese, because of body composition and airway anatomy, forces necessary to visualize entrance to larynx using standard laryngoscopes are significantly higher, thus the workload during intubation attempts is increased [20]. New ergonomic devices for airway management may improve situation.…”
Section: Discussionmentioning
confidence: 99%
“…but more intubation efforts (average 1.4) [17]. We evaluated the C-MAC videolaryngoscope (Storz, Germany) in morbidly obese patients and we found that it improved the laryngeal view [9]. In this study and the presented study, all cases of the intubation were successful within the recommended time for intubation attempts, which is especially important in morbidly obese patients, in whom desaturation is faster than that in nonobese patients [18].…”
Section: Discussionmentioning
confidence: 85%
“…The use of videolaryngoscopes should improve laryngeal view in morbidly obese patients [8, 9]. Although obesity alone is not a risk factor for difficult intubation [10], it is recommended to use videolaryngoscopes as a part of routine practice in anesthesia for morbidly obese patients [11].…”
Section: Introductionmentioning
confidence: 99%